2018
DOI: 10.3390/toxins10070254
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review for Evidence of Aphanizomenon flos-aquae Toxigenicity in Recreational Waters and Toxicity of Dietary Supplements: 2000–2017

Abstract: Previous studies of recreational waters and blue-green algae supplements (BGAS) demonstrated co-occurrence of Aphanizomenon flos-aquae (AFA) and cyanotoxins, presenting exposure risk. The authors conducted a systematic literature review using a GRADE PRISMA-p 27-item checklist to assess the evidence for toxigenicity of AFA in both fresh waters and BGAS. Studies have shown AFA can produce significant levels of cylindrospermopsin and saxitoxin in fresh waters. Toxicity studies evaluating AFA-based BGAS found som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 66 publications
0
26
0
Order By: Relevance
“…43 A recent systematic literature review assessing the safety of AFA in dietary supplements revealed that many AFA supplements are contaminated with cyanotoxins, which are harmful toxins to the liver, nervous system, and skin in humans and advised caution for using AFA supplements. 44…”
Section: Discussionmentioning
confidence: 99%
“…43 A recent systematic literature review assessing the safety of AFA in dietary supplements revealed that many AFA supplements are contaminated with cyanotoxins, which are harmful toxins to the liver, nervous system, and skin in humans and advised caution for using AFA supplements. 44…”
Section: Discussionmentioning
confidence: 99%
“…Microalgae own antiviral, antibacterial, anti‐HIV, anticancer, and numerous neurological actions 112,192–195 . Dinoflagellates and BGA produce extremely effective toxins such as Microcystins 193 . Toxins produced by BGA, Prymnesium parvum sp., and Ochromonas sp.…”
Section: Advanced Integrated Biorefinery Scheme To Produce Algae‐based Productsmentioning
confidence: 99%
“…The adverse effects of a strain of Aphanizomenon issastchenkoi (LMECYA31), producing saxitoxins, on the survival and somatic growth of Daphnia magna were found (Nogueira et al, 2004). STX is also capable of entering the human body via a cut or other open wound, and the predicted human LD 50 based on previous mice studies, via this route of exposure, has been estimated to be 50 μg/kg body weight (Lyon-Colbert et al, 2018). Currently, the acute RfD (acute reference dose), used in place of the noobserved-adverse-effect level, is 0.5 μg STX equivalent/kg-day (Chain, 2009).…”
Section: Saxitoxinmentioning
confidence: 99%